'Listening Back': Exploring the Sonic Interactions at the Heart of Historical Sound Effects Performance. Issue 1 (March 2017) - Keenan, Fiona; Pauletto, Sandra
Abstract : The cinematic sound design practice of Foley developed from a rich history of performative sound design through materials, objects and mechanical devices created for theatrical performance, magic lantern shows and silent cinema screenings in the late nineteenth and early twentieth century. Now, as virtual and digital methods become available in film sound design production, it is time to evaluate the contribution of these historical sound design methods through the discipline of Sonic Interaction Design (SID). Exploring the use of everyday objects and sound effects devices in the creation of a soundtrack allows us to 'listen' back and forward simultaneously. Our knowledge of historical sound practice can be updated and new practices can be generated, at the same time deepening our understanding of sound for screen that is performative in nature. This article investigates the interactivity inherent in historical sound effects performance through a case study of a mechanical and digital wind machine reconstruction, and explores its potential to inform new interactive digital methods for sound design.